Pengaruh Variabel Demografi Terhadap Pertumbuhan Ekonomi Provinsi Nusa Tenggara Barat Tahapan Menuju Bonus Demografi - Arini, Gusti Ayu; Chaidir, Taufiq; Satarudin, Satarudin; Sriningsih, Siti (Jurnal Ekonomi dan Bisnis, 2018)
The study entitled The Influence of Demographic Variables on the Economic Growth of the Province of West Nusa Tenggara towards the Demogerafi Bonus aims to analyze the variables of population growth, number of workers, dependency ratio, the level of participation of women labor force towards economic growth in West Nusa Tenggara province. This type of research is descriptive research and uses secondary data for the period 2009-2016. To analyze the relationship of variables Population growth, labor, dependency ratio and the level of participation of the female labor force towards the economic growth of the province of West Nusa Tenggara were used multiple linear regression model with the Ordinary Least Square (OLS) method. The results obtained from this regression for the population growth variable (X1) and dependency ratio (X3) have a negative slope giving meaning if there is an increase in population growth and dependency ratio, there is a tendency to decrease economic growth while for the variable labor (X2) and participation rate the female workforce (X4) has a positive slope giving meaning, if there is an increase in the number of workers and the level of participation of the female workforce, there is a tendency to increase economic growth. The test is partially and simultaneously all significant. The level of suitability (the goodness of fit) of the observed estimation model is indicated by the coefficient of determination (R2) of 0.894. This means that the ability and contribution of the independent variables observed in the dependent variable is 89.4 percent while the remaining 10.6 percent is outside the model.